2011
DOI: 10.1055/s-0030-1270920
|View full text |Cite
|
Sign up to set email alerts
|

hERG Channel Inhibitors in Extracts of Coptidis Rhizoma

Abstract: Inhibition of the hERG channel delays repolarization and prolongs the QT interval and cardiac action potential which can lead to sudden death. Several drugs have been withdrawn from the market due to hERG channel inhibition. In the search of hERG channel inhibitors of natural origin, we established an HPLC-based profiling approach which combines HPLC-microfractionation and bioactivity testing on Xenopus laevis oocytes. The methanolic extract of the TCM herbal drug Coptidis rhizoma (Coptis chinensis Franch., Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
(42 reference statements)
0
31
0
Order By: Relevance
“…7 For a broader risk assessment, we recently screened a selection of widely used food and medicinal plants 10 and identified the major alkaloid dihydroberberine in the traditional Chinese herbal drug Huanglian (rhizome of Coptis chinensis Franch., Ranunculaceae) as a compound with mild hERG-inhibitory properties in the Xenopus oocyte assay. 11 As a follow-up, we screened a diverse collection of alkaloids found in medicinal plants and identified additional alkaloids with in vitro hERGblocking properties. 8 We extended the assessment of possible hERG liabilities by screening an extract library generated from 142 medicinal plants used in southern Africa.…”
mentioning
confidence: 99%
“…7 For a broader risk assessment, we recently screened a selection of widely used food and medicinal plants 10 and identified the major alkaloid dihydroberberine in the traditional Chinese herbal drug Huanglian (rhizome of Coptis chinensis Franch., Ranunculaceae) as a compound with mild hERG-inhibitory properties in the Xenopus oocyte assay. 11 As a follow-up, we screened a diverse collection of alkaloids found in medicinal plants and identified additional alkaloids with in vitro hERGblocking properties. 8 We extended the assessment of possible hERG liabilities by screening an extract library generated from 142 medicinal plants used in southern Africa.…”
mentioning
confidence: 99%
“…However, several studies have demonstrated that berberine [6][7][8][9], chelerythrine [10], chelidonine [11], sanguinarine [11], and protopine [11] have hERG ion channel activities. The human ether-à-go-go-related gene (hERG, KCNH2, Kv11.1) encodes a cardiac voltage-gated potassium channel that provides the major repolarizing current (rapidly activating delayed rectifier potassium current, I Kr ) in phase 3 of the cardiac action potential.…”
Section: Introductionmentioning
confidence: 99%
“…Among these alkaloids, berberine was reported to inhibit hERG potassium current in transfected HEK cells expressing hERG channels [7][8][9], to block delayed rectifier potassium (I Kr ) current in cardiac myocytes [6], and to increase action potential duration on cardiac preparations [6,7]. Chelerythrine was also described to inhibit hERG current [10] and prolong action potential [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some researches proved that use of BBR combined with antibacterial agents (azithromycin, cefazoline and levofloxacin) was against clinical Multi-Drug resistant isolates of Methicillin-Resistant Staphylococcus aureus (MRSA) (Zuo et al, 2012). Several studies indicated that BBR and CLR inhibited hERG currents (Nilsson and Webster, 2014;Schramm et al, 2011). All macrolide antibiotics except AZM are metabolized by the liver.…”
Section: Introductionmentioning
confidence: 99%